Ritual landscapes and borders within rock art research : papers in honour of Professor Kalle Sognnes - Stebergløkken, Heidrun,; Berge, Ragnhild,; Lindgaard, Eva,; Stuedal, Vangen,; Sognnes, Kalle, (Archaeopress Publishing Ltd, 2015)
Ritual landscapes and borders are recurring themes running through Professor Kalle Sognnes' long research career. This anthology contains 13 articles written by colleagues from his broad network in appreciation of his many contributions to the field of rock art research.